Spiritual Values of Characters in the Novel Percumbuan Topeng by S. Prasetyo Utomo and Their Relevance to Literature Learning in High School - Yuniarti, Yuniarti; Agus Nuryatin; Mukh. Doyin (Universitas Negeri Semarang, 2024)
The novel Percumbuan Topeng by S. Prasetyo Utomo is a novel that contains spiritual values that are reflected in the behavior of its characters. This study aims to analyze the spiritual values of the characters in the novel Percumbuan Topeng by S. Prasetyo Utomo, to explain the forms of needs that influence the spiritual values of the characters in the novel Percumbuan Topeng by S. Prasetyo Utomo and to explain the relevance of spiritual values in the novel Percumbuan Topeng by S. Prasetyo Utomo to literature learning in high school. This study uses a content analysis model (content analysis). The steps taken are to review documents, record data, and classify or group data that contains spiritual values. Based on the results of data analysis, spiritual values were found in the novel Percumbuan Topeng including the values of patience, caring, obeying parents, calm, grateful, simple, diligent, honest, sincere, sincerity, steadfastness, religious, having a sense of trust, patience, daring to admit mistakes, being obedient in worship, enthusiasm, simplicity, and loyalty. The results of the study indicate that there are spiritual values that are useful in learning literature to instill attitudes that can be emulated by students in everyday life.